(untitled) (Teacher’s World: Journal of Education and Research, 2023)
The mixed-method study aims at exploring the effectiveness of rubrics towards authentic assessment of language learning in higher education by understanding the role of the rubric. In the recent trend and style of language teaching-learning, the rubric is one of the important tools that design the set standards and criteria which teachers use to assess students’ performance, assignment or behavior. In educational technology, a rubric is the performance standard for a student population typically having four essential components: task description, the scale of achievement, dimensions and description of dimensions. The type of rubric is chosen from the range of holistic rubrics, analytic rubrics, generic rubrics or specific rubrics for assessment depending on the task being evaluated and the needs of the assessor. Research says that the rubric helps to define “quality performance” and promote awareness on critical components in a performance not only acting as an evaluation tool for instructors but also acting as a feedback proforma for students. According to the rubric experts, rubrics are vital tools that can be utilized to solve the problem of subjectivity in the evaluation as they provide consistency in evaluation, reduce subjectivity and enhance objectivity. To explore the real scenario, the researcher collected data through the analysis of students’ performance in two classes where the teachers used the rubric and in two classes where the teachers did not use it. Besides, a semi open-ended questionnaire was administered among four teachers, two of each category to see their perspectives about the impact of rubrics in reducing subjectivity. Alongside, four FGD were conducted to put light on students’ perceptions. The result shows a significant impact of rubrics on students’ performance along with a strong positive attitude of both students and teachers towards the use of rubrics. A wide scope of further research is open in this area. Teacher’s World: Journal of Education and Research, Vol. 48(2), Dec 2022, p.112-129